Impacto da política afirmativa de costas para afro descendentes na faculdade Salesiana Dom Bosco - Silva, Arlete Oliveira Conceiçao da (2011)
The process of discussion on the ethnic-racial diversity that has been occurring throughout the world, has occurred in Brazil in various sectors of society. This study is conducted historical review of the situation of african descent, from the several moments in which they were forbidden (by law) the right to education, the level of socio-economic imbalances affecting this portion of the population by the current policies of character so that aim to tackle prejudice and racism still present in society today. Education is seen as an instrument of social transformation, and higher education appointed as a possibility for social mobility, providing opportunities for strengthening the self-identification and increased self-esteem of so-called social minorities who are excluded. The african descendent and their access to higher education is the central problem of the study. Among the public policies of affirmative action under the Education stands out the Program University for All - PROUNI, created on 10/09/2004 by a provisional measure No. 213 and institutionalized by law 11. 096/2005, to offer scholarships at private colleges, for people without advanced degrees, with low-income public school students and to reserve places for african descent and indigenous peoples. The program focuses on training professionals who can serve their peers as an incentive and motive of self-assertion. For this to happen it is necessary that the educational institutions that deploy PROUNI, are available, as are managers prepared to follow its development. To sum up the impact of the research (in its positive aspects and difficulties) occurred in the implementation and monitoring of the program at an institution of higher education-IES from Manaus - AM, from the perspective of managing the program, managers and the IES fellows of the academics involved. We used interviews, meetings, informal contacts and desk research as well as literature on the subject. The process of data analysis interrelate the various sources of information providing a broader perspective of the reality studied. The results obtained indicate a coincidence between some of the goals of IES and PROUNI demonstrate the need for more knowledge about the program. The impact of greater importance that the search highlighted what was to introduce quotas for african descent, the IES has made the problems of this population gain visibility and had to be addressed, assuming all locks and prejudices naturalized by society.